Simulação numérica do movimento de água e solutos em solos não saturados - Campos, Ângelo Antônio (2007)
The interest in studying problems of underground drainage and solutos transport not in soils saturated it has been increasing significantly in the last years, mainly because of the growing concern with the quality of the soil and of the environment in gen